The Role of Digitization in Empowering MSMEs and Enhancing Local Economy in Cimalaka Village, Sumedang: Peran Digitalisasi dalam Memberdayakan UMKM dan Meningkatkan Ekonomi Lokal di Desa Cimalaka, Sumedang - Dewi, Sofia; Saepuloh, Asep; Aprilia, Yulianti; Komalasari, Esti; Saripah, Ipah; Lidinillah, Siti Habibah (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
This community service investigated the contribution of digitalization to increasing income and expanding the market in Cimalaka Village, and identified barriers and potential development opportunities. Local MSMEs still face limitations in marketing and competitiveness. Digitalization was offered as a solution through a qualitative approach with mentoring experiments. The digitalization activities implemented included logo creation, product catalogs, registration on Google Maps, halal certification, and the use of QRIS as a digital payment system. The results of this activity showed a significant increase in the visibility, credibility, and market reach of MSMEs. Before the program, most MSMEs lacked a clear business identity, had not utilized social media, and still relied on cash transactions. After outreach and mentoring, 11 MSMEs successfully developed business logos, product catalogs, active social media accounts, and began using QRIS and were registered on Google Maps. This digital role has been proven to facilitate business promotion, transactions, and management, thus driving increased revenue. However, obstacles remain such as low technological literacy and a lack of outreach. This activity contributes to the community while providing practical guidance for effective and sustainable MSMEs.